School attendance and literacy before the famine: A simple baronial analysis - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2010)
This paper complements a much larger study of school attendance in pre-famine Ireland by FitzGerald (2010). It exploits some of the data generated by that study to analyze further some of the determinants of schooling and literacy in the 1820s and 1840s.
hdl:10197/2647
Keywords: 330; Ireland; Economic history; Literacy; Human capital